2020
DOI: 10.2147/ott.s242300
|View full text |Cite
|
Sign up to set email alerts
|

<p>Long Noncoding RNA MALAT1 Promotes the Development of Colon Cancer by Regulating <em>miR-101-3p</em>/STC1 Axis</p>

Abstract: Purpose: Colon cancer (CC) is a leading cause of cancer-related deaths worldwide. This study aimed to clarify the effect of long noncoding RNA (lncRNA) metastasis-associated lung adenocarcinoma transcript 1 (MALAT1) on CC progression and the potential mechanism. Methods: CC cell lines HCT116 and HT29 were selected for functional analysis. The expression of MALAT1, microRNA (miR)-101-3p, and stanniocalcin 1 (STC1) in CC tissues and cells were measured by quantitative reverse transcription PCR (qRT-PCR). Cell pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 49 publications
1
14
0
Order By: Relevance
“…Applying in vitro experiments using clinical cancer tissues and cancer cell lines, we observed that overexpression of the lncRNA MALAT1 in EOC cells encouraged drug resistance, invasion, and migration through adaptive remodeling strategies that promote tumor cell survival and proliferation, combined with the inhibition of cellular immunity and apoptosis in the TME, hence triggering EOC tumor progression. Our investigation also revealed that MALAT1 was highly expressed among carcinoma tissues from various organs, including EOCs, as previously reported [ 26 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ]. Mechanistically, the activity of MALAT1 in transcriptional regulation showed that MALAT1-knockdown inhibited the oncogenic function in RCC and consistently depleted histone methyltransferase e nhancer of z este h omology 2 (EZH2), a histone lysine N-methyltransferase enzyme (EC 2.1.1.43), resulting in the inhibition of the EMT through the recovery of E-cadherin and a downregulation of β-catenin [ 40 ].…”
Section: Discussionsupporting
confidence: 89%
“…Applying in vitro experiments using clinical cancer tissues and cancer cell lines, we observed that overexpression of the lncRNA MALAT1 in EOC cells encouraged drug resistance, invasion, and migration through adaptive remodeling strategies that promote tumor cell survival and proliferation, combined with the inhibition of cellular immunity and apoptosis in the TME, hence triggering EOC tumor progression. Our investigation also revealed that MALAT1 was highly expressed among carcinoma tissues from various organs, including EOCs, as previously reported [ 26 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ]. Mechanistically, the activity of MALAT1 in transcriptional regulation showed that MALAT1-knockdown inhibited the oncogenic function in RCC and consistently depleted histone methyltransferase e nhancer of z este h omology 2 (EZH2), a histone lysine N-methyltransferase enzyme (EC 2.1.1.43), resulting in the inhibition of the EMT through the recovery of E-cadherin and a downregulation of β-catenin [ 40 ].…”
Section: Discussionsupporting
confidence: 89%
“…Another study demonstrated that STC1 can promote the invasion of breast cancer cells [ 43 ]. In colon cancer, the lncRNA-MALAT1/miR-101-3p/STC1 axis can promote the development of the tumor [ 44 ]. So, STC1 was regarded as the potential candidate for further analysis.…”
Section: Discussionmentioning
confidence: 99%
“…These studies suggest that miR-101–3p may be an important tumour-associated gene, with potential in drug development. In LC, miR-101–3p has generally been studied as a common targeting site for long-noncoding-RNA MALAT1 [ 8 ] or SNHG6 [ 16 ], implying that it may have an important therapeutic role. However, its expression level and actual therapeutic effect in LC, as well as its oncological therapeutic mechanism, have not been reported.…”
Section: Discussionmentioning
confidence: 99%